Research Methods and Statistics in Psychology / Sixth Edition - Coolican Hugh (Psychology Press, Ltd, 2014)
This book covers four topics for the price of one and is essential reading for psychology students at all levels from first-year undergraduate to Master's. Psychology and Science and Research, Measuring People - Variables and Samples and the Qualitative Critique, Experiments and Experimental Designs in Psychology, Validity in Psychological Research, Quasi-Experiments and Non-Experiments, Observational Methods - Watching and Being with People, Analyzing Qualitative Data, Statistics - Organizing the Data, Frequencies and Distributions, Testing the Differences Between Two Samples, Correlation and Regression, Multi-Factorial ANOVA Designs, Choosing a Significance Test for your Data, Planning your Practical and Writing up Your Report.